Biobased porous acoustical absorber made from polyurethane and waste tires particles - Soto, Guillermo (2016)
The production of flexible polyurethane foams (FPF) incorporating bio/recycled raw materials is an interesting alternative to conventional acoustic absorbent materials. In this sense, bio-based polyols like glycerol or hydroxylated methyl esters derived from tung oil as multifunctional polyols, and waste tires particles as fillers with capability for acoustical absorption and low thermal conductivity, are prospective feedstocks for FPF preparation. In this work, FPF were prepared by adding different amounts of these components to a formulation based on a commercial polyether polyol. Results of normal sound absorption coefficient measurements at different frequencies, scanning electron microscopy analysis and compression tests are presented and discussed. The addition of waste tires particles or glycerol to the commercial formulation gives good performance as acoustic absorbers from 400 500 Hz, with NRC and SAA values near and above 50%. Moreover, the absorption coefficient reaches high values mostly at the highest evaluated frequencies (~62-89% at 2000 Hz and ~70-91% at 5000 Hz), for 30 mm thickness samples. On the other hand, the obtained FPF presented enhanced both the modulus and yield stress and in all the cases, a high recovery of the strain (>90%) applied in compression tests was attained after 24 hours. Scanning electron microscopy micrographs revealed that the obtained foams present a combination of open and closed cell structures and both, the modifiers and particles, tend to decrease the cell size. Based on acoustical and mechanical performance, and morphological analysis, the results show that these new kind of materials could be innovative sound absorbers, cheaper and environmentally more convenient in comparison with other available materials.